2017
DOI: 10.1155/2017/1201404
|View full text |Cite
|
Sign up to set email alerts
|

A Patency Capsule Remained Intact in the Colon over 210 Hours

Abstract: We present an unusual case of a 35-year-old male patient whom a patency capsule stayed in his gut without breaking. He has a history of Peutz-Jeghers syndrome and multiple abdominal surgeries. Prestudy was performed for abdominal searching, but a patency capsule remained in the colon over 9 days. He displayed neither abdominal nor obstructive symptoms in that period. We collected the patency capsule using colonoscopy after dilating a postoperative stricture at an anastomotic site of the rectum. Clinicians shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Out‐of‐spec variations in PC dissolution time may be caused by too much or too little exposure to intestinal fluids, or by chewing the PC during ingestion. Some case reports have described a lack of PC dissolution because of low exposure to intestinal fluids 8 . In our case, the patient took Patency capsules at home after careful explanation and consent.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Out‐of‐spec variations in PC dissolution time may be caused by too much or too little exposure to intestinal fluids, or by chewing the PC during ingestion. Some case reports have described a lack of PC dissolution because of low exposure to intestinal fluids 8 . In our case, the patient took Patency capsules at home after careful explanation and consent.…”
Section: Discussionmentioning
confidence: 77%
“…Some case reports have described a lack of PC dissolution because of low exposure to intestinal fluids. 8 In our case, the patient took Patency capsules at home after careful explanation and consent. Although medical personnel could not be present, the patient was a middle‐aged man without dementia with no problematic behavior regarding swallowing the Patency capsules, such as chewing the PCs.…”
Section: Discussionmentioning
confidence: 78%
“…The maximum excretion time of intact capsule was 68 h after ingestion in our study. Surprisingly, Hihara et al [18] reported a case with excretion of an intact capsule > 210 h after PPC ingestion. They mean that the starting time for dissolution of timer plug is variable and that Following CE, the PPC was observed in the pelvis minor in an AXR or CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…12 Tag-less PC-associated AEs, such as aspiration, residual parylene coating, SBO, prolonged disintegration, and perforation, have been reported only in case reports. [13][14][15][16][17][18][19] Therefore, we aimed to evaluate tag-less PC-related AEs in more detail for the appropriate use of the PC in the J-POP study and additional research among a total of 2578 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous multicenter prospective study (the Japanese Association for Capsule Endoscopy Survey on the Appropriate Use of the Patency Capsule [J‐POP] study) demonstrated that CE retention occurred in 0.51% of the enrolled 1096 patients 12 . Tag‐less PC‐associated AEs, such as aspiration, residual parylene coating, SBO, prolonged disintegration, and perforation, have been reported only in case reports 13–19 . Therefore, we aimed to evaluate tag‐less PC‐related AEs in more detail for the appropriate use of the PC in the J‐POP study and additional research among a total of 2578 patients.…”
Section: Introductionmentioning
confidence: 99%